Stochastic multi-stage optimization : at the crossroads between discrete time stochastic control and stochastic programming /: at the crossroads between discrete time stochastic control and stochastic programming. (2015) - Carpentier, Pierre; Chancelier, Jean-Philippe; Cohen, Guy; De Lara, Michel, 1961-
No abstract available